2018
DOI: 10.1021/acsami.7b16127
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Ga2O3 Anode for Lithium-Ion Batteries

Abstract: There is a great deal of interest in developing battery systems that can exhibit self-healing behavior, thus enhancing cyclability and stability. Given that gallium (Ga) is a metal that melts near room temperature, we wanted to test if it could be employed as a self-healing anode material for lithium-ion batteries (LIBs). However, Ga nanoparticles (NPs), when directly applied, tended to aggregate upon charge/discharge cycling. To address this issue, we employed carbon-coated GaO NPs as an alternative. By contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 49 publications
2
58
0
Order By: Relevance
“…This reaction mechanism including rst intercalation, conversion reaction and alloy process are similar to previous reports in Ga 2 O 3 , Ga 2 S 3 , CoGa 2 S 4 and NiGa 2 O 4 , etc. 14,19,21,36 Fig . 3b shows the galvanotactic discharge-charge (GDC) prole for the rst three cycles at a current density of 0.5 A g À1 , in which the GaOOH electrode shows a discharging capacity of 1343 mA h g À1 and charging capacity of 602 mA h g À1 upon the initial cycle, with coulombic efficiency of 45%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This reaction mechanism including rst intercalation, conversion reaction and alloy process are similar to previous reports in Ga 2 O 3 , Ga 2 S 3 , CoGa 2 S 4 and NiGa 2 O 4 , etc. 14,19,21,36 Fig . 3b shows the galvanotactic discharge-charge (GDC) prole for the rst three cycles at a current density of 0.5 A g À1 , in which the GaOOH electrode shows a discharging capacity of 1343 mA h g À1 and charging capacity of 602 mA h g À1 upon the initial cycle, with coulombic efficiency of 45%.…”
Section: Resultsmentioning
confidence: 99%
“…11 Sn, Sb, Ge, Si and Ga metal candidates, which can alloy with Li, seem to be the optimal choice. Ga exhibits a unique liquid nature at room temperature with reported self-healing ability, [12][13][14][15] which can repair electrode cracks by surface tension upon lithiation reactions. 16 Moreover, the alloy reactions between Li and Ga undergo the following reversible process: Ga 4 Li 2 Ga 7 4 LiGa 4 Li 2 Ga, 17 thus delivering a theoretical capacity of $768 mA h g À1 from Li 2 Ga, about twice as much as commercial graphite anode.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast with the Ga bulk, Ga nanoparticles exhibited higher rate capacities (about twice of the bulk ones). Controlling the pH values of precursor solutions, Tang et al synthesized Ga 2 O 3 @C particles with different particle sizes and specific surface areas [72], conversing that the sample featured with smaller particle size and larger specific surface area had higher capacity. Building nano-architectures, such as three dimensional (3D) nanosheets, 3D network nanowires and framework-templated nanosheets/nanoparticles, is an alternative path to nanostructure design [20,33,[73][74][75][76][77][78][79].…”
Section: Modification Strategies For Gallium-based Anodesmentioning
confidence: 99%
“…Gallium oxide, with a wide bandgap (E g ) in the range of 4.9-5.2 eV, is a crucial semiconducting material, which has drawn great attention and investigation in the field electronic and photoelectronic [104][105][106][107]. Given the merits of gallium in the field of energy storage, researchers are particularly interested in its oxide derivative with chemical formula of Ga reported the synthesis of highly dispersed Ga 2 O 3 nanoparticles capped with carbon layer (Ga 2 O 3 @C) using a hydrothermal carbonization method and calcination treatment under an argon atmosphere [72]. X-Ray diffraction (XRD) characterization for Ga 2 -O 3 @C indicated that it belongs to a face-centered cubic structure, which was denoted as c-Ga 2 O 3 .…”
Section: Gallium Oxide Anodesmentioning
confidence: 99%
“…The methodology is depicted in Figure 2B. 34 We summarize key features associated with the use of Ga oxides in this example. The particles are prepared via a hydrothermal carbonization method that controls their size to 2.6 nm and ensures the formation of a carbon shell around each particle.…”
Section: Applied Interfaces Based On Ga Containing Oxides In Aqueous mentioning
confidence: 99%